Evaluating reality of modern teaching strategies used by faculty members in teaching methods in physical education subject from perspective of third-year students at Department of Physical Education and Sports Sciences - Zaki Mardan Omar (Journal of Applied Movement and Sport Science, 2026)
Background Teaching methods in education is a crucial subject that plays a significant role in improving students' levels and capabilities, particularly upon graduation and their integration into teaching process. It also helps them learn how to interact with students and deliver curriculum effectively. The use of modern teaching strategies by teachers plays a major role in developing students' higher-order thinking skills, which aligns with essential requirements of active learning, a student-centered approach. Teaching strategies at Department of Physical Education and Sports Science are acquired due to nature of subjects, which are always a blend of theoretical and practical material. Objectives The study aimed to accurately identify current practices used by faculty members in subject of teaching methods to ensure correct application of modern teaching strategies. It also aimed to identify strengths and weaknesses in areas where these modern teaching strategies are effective or weak, and to offer suggestions and recommendations for improving teaching methods based on findings. Methods The study focused on third-year students at Department of Physical Education and Sports Sciences, and on 155 students (male and female), representing 100% of sample. Population was selected from third-year students enrolled in morning program at Department of Physical Education and Sports Sciences, College of Basic Education, Al-Mustansiriya University. Sample was distributed across different groups. The study recommended necessity of training faculty members in modern teaching strategies and their practical application within teaching methods course at Department of Physical Education and Sports Sciences. Results The study recommended necessity of training faculty members in modern teaching strategies and their practical application within teaching methods course at Department of Physical Education and Sports Sciences. It also recommended encouraging faculty members to diversify their motivational and discussion methods to ensure and facilitate participation of all students in educational process and to stimulate their critical and creative thinking. Conclusion Finally, it recommended improving academic supervision programs and facilitating exchange of expertise among faculty members to share best practices in implementing active and collaborative learning strategies. Need to use modern educational technologies within classroom in a way that is consistent with and helps philosophy of active education and increases student interaction and comprehension of material.